Faculty and student research in practicing academic freedom - Sengupta, Enakshi; Blessinger, Patrick (Innovations in higher education teaching and learning, 2020)
Includes case studies from Turkey, Iraq, Pakistan and Hungary, the authors in this edited collection examine the role of racial and gender biases, paired against rights and responsibilities, to highlight the drivers of restrictions on academic freedom against a backdrop of globalisation.